AKAD AL-IJARAH AL-MUNTAHIYAH BIT TAMLIK (IMBT) - Qusthoniah, Qusthoniah; Sari, Nurmala (Syari'ah, 2020)
One of the contracts that is interesting to discuss is the ijarah (lease) contract, which is also a contract that is often used in every day life. It is also interesting to discuss, because in this contract there will be modifications and change due to human needs. One of the changes in the form of this lease agreement is the Ijarah Al-Muntahiyah Bi al-Tamlik (IMBT) contract or also known as Al-Ijarah Thumma Al-Ba’i –AITAB- (rent then buy) and hire and purchase. This contract uses two contract in separate ways, namely the lease contract (ijarah/leasing or renting), and the sale and purchase contract (ba’i/purchase). The IMBT contract is similar to the conventional lease agreement which is very popular lately it can be said that IMBT is sharia based leasing.